Lower-ischemic-risk profile of coated flow redirection endoluminal device X compared with uncoated flow redirection endoluminal device flow diverter in the treatment of unruptured intracranial aneurysms - Görtz, Lukas; Hohenstatt, Sophia; Vollherbst, Dominik; Styczen, Hanna; Siebert, Eberhard; Bohner, Georg; Deuschl, Cornelius; Möhlenbruch, Markus Alfred; Kabbasch, Christoph (Neurosurgery, 2025)
BACKGROUND AND OBJECTIVES: - Flow Redirection Endoluminal Device (FRED) X is a new generation flow diverter with an antithrombotic surface coating. This study compares the procedural safety and short-term efficacy of FRED X with its uncoated predecessor, the FRED. - METHODS: - Patients treated with FRED and FRED X devices for unruptured aneurysms between 2013 and 2023 at 3 neurovascular centers were retrospectively reviewed. The procedural ischemic event rate was the safety end point, and the complete aneurysm occlusion rate at 1 year was the efficacy end point. Multivariable regression adjustment and 1:1 propensity score matching were performed to control for potential confounding. - RESULTS: - The FRED X group (137 patients) had a higher prevalence of recurrent and bifurcation aneurysms and fewer aneurysms with branch involvement than the FRED X group (156 patients). The ischemic event rate was lower in FRED X (1/156 [0.6%]) than in FRED (7/137 [5.1%]), which was significant after multivariable adjustment (odds ratio: 8.8, 95% CI: 1.1-72.7, P = .04), and tended to be significant in the propensity score analysis (P = .07). Morbidity was comparable between FRED (2.2%) and FRED X (0%, P = .10). The complete occlusion rates of FRED vs FRED X were 73/117 (62.4%) vs 39/54 (72.2%) aneurysms at 6 months (P = .21) and 52/74 (70.3%) vs 27/37 (73.0%) at 12 months (P = .77). Hemorrhagic complications, in-stent stenosis, and clinical events during follow-up and retreatments were not significantly different between groups. - CONCLUSION: - This study indicates an improved ischemic risk profile of FRED X while maintaining a favorable efficacy profile, warranting further study and translation into clinical use.
Online veröffentlicht: 8. Oktober 2024
Gesehen am 02.10.2025